2014
DOI: 10.7554/elife.04047
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes refine cortical connectivity at dendritic spines

Abstract: During cortical synaptic development, thalamic axons must establish synaptic connections despite the presence of the more abundant intracortical projections. How thalamocortical synapses are formed and maintained in this competitive environment is unknown. Here, we show that astrocyte-secreted protein hevin is required for normal thalamocortical synaptic connectivity in the mouse cortex. Absence of hevin results in a profound, long-lasting reduction in thalamocortical synapses accompanied by a transient increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
151
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(169 citation statements)
references
References 55 publications
14
151
0
4
Order By: Relevance
“…For example, in the antennal lobe of Drosophila the morphology and connectivity of local interneurons can vary between animals and may require NG to respond accordingly (Chou et al, 2010). Finally, NG may also play an important role in maintaining axons and in monitoring and pruning synapses to ensure the proper number and type of synaptic connections, as they do in invertebrates (O’Connor et al, 2017) and vertebrates (Risher et al, 2014), respectively, during normal development and after injury (Burda et al, 2016; He and Jin, 2016; Stephan et al, 2012). Glial developmental plasticity may be essential to achieve robustness and maintain homeostasis by readily adapting to these and perhaps other variations in nervous system size and morphology.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the antennal lobe of Drosophila the morphology and connectivity of local interneurons can vary between animals and may require NG to respond accordingly (Chou et al, 2010). Finally, NG may also play an important role in maintaining axons and in monitoring and pruning synapses to ensure the proper number and type of synaptic connections, as they do in invertebrates (O’Connor et al, 2017) and vertebrates (Risher et al, 2014), respectively, during normal development and after injury (Burda et al, 2016; He and Jin, 2016; Stephan et al, 2012). Glial developmental plasticity may be essential to achieve robustness and maintain homeostasis by readily adapting to these and perhaps other variations in nervous system size and morphology.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown to be the case for Hevin. In the developing mouse cortex, Hevin is specifically required for the formation of a subset of excitatory synapses: the thalamocortical connections between thalamic axons and cortical dendrites (Risher et al, 2014). Investigation of the ultrastructure of cortical dendrites at high resolution revealed that astrocyte-secreted Hevin is required for a developmental refinement step that occurs at the level of single dendritic spine heads.…”
Section: Astrocytic Control Of Synapse Developmentmentioning
confidence: 99%
“…As synapses mature the spines lose one of these inputs and keep the other, achieving the characteristic “one spine = one synapse” organization. Absence of Hevin results in persistence of dendritic spines which are still doubly innervated, most likely due to the inability of thalamocortical connections to compete for spines with cortical inputs (Risher et al, 2014). …”
Section: Astrocytic Control Of Synapse Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Astrocytes have been found to be important in presynaptic muting of hippocampal neurons, again through their expression of thrombospondins (Crawford et al, 2012). Another astrocyte-secreted protein, hevin, has been implicated in regulating cortical connectivity during development by refining dendritic spines (Risher et al, 2014). They also play a role in targeting synapses for elimination (Stevens et al, 2007).…”
Section: Normal Functions Of Astrocytesmentioning
confidence: 99%